2015
DOI: 10.1177/0148607115594674
|View full text |Cite
|
Sign up to set email alerts
|

How Close Are We to Achieving Energy and Nutrient Goals for Very Low Birth Weight Infants in the First Week?

Abstract: Despite the introduction of more aggressive early feeding guidelines and improved energy and nutrient intakes compared with literature values, many VLBW infants remain below recommended nutrition goals in the first week.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 48 publications
0
30
0
2
Order By: Relevance
“…Mean protein intakes during the first week were approximately 3.2 g/kg/d in their studies, which is higher than we have reported (2.9 g/kg/d; Figure and http://journals.sagepub.com/doi/suppl/10.1177/0148607117710441). We previously reported that by the end of the first week of life, 70% of exclusively mother’s milk‐fed infants from our cohort had not yet achieved recommended protein intakes of 3.8 g/kg/d . Importantly, Senterre and Rigo showed that the cumulative protein deficit during the first week of life was the major determinant of weight gain during the first 6 weeks of life …”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Mean protein intakes during the first week were approximately 3.2 g/kg/d in their studies, which is higher than we have reported (2.9 g/kg/d; Figure and http://journals.sagepub.com/doi/suppl/10.1177/0148607117710441). We previously reported that by the end of the first week of life, 70% of exclusively mother’s milk‐fed infants from our cohort had not yet achieved recommended protein intakes of 3.8 g/kg/d . Importantly, Senterre and Rigo showed that the cumulative protein deficit during the first week of life was the major determinant of weight gain during the first 6 weeks of life …”
Section: Discussionmentioning
confidence: 78%
“…However, it needs to be acknowledged that the causal pathways among individual morbidities and between morbidity and suboptimal nutrition are complex and often bidirectional. For example, suboptimal nutrition may increase the likelihood of sepsis, and a bout of sepsis may result in slower advancement or suspension of enteral feeding . Recent findings from both the Swedish and the U.S. ELGAN cohorts report that suboptimal energy and lipid intakes are associated with a higher risk of developing ROP .…”
Section: Discussionmentioning
confidence: 99%
“…4. En los RNPT existe evidencia de que alcanzar los objetivos calóricos y proteicos precozmente (Tablas II y III), mejora la evolución clínica, reduce la restricción del crecimiento y favorece el neurodesarrollo, por lo que se recomienda una nutrición intensiva desde los primeros días (19,20). Se recomienda iniciar la NP aportando 60 kcal/kg/día, con incrementos hasta 90-100 kcal/kg/día en la primera semana y hasta 120 a la tercera semana (21,22) (Tabla II).…”
Section: Circunstancias Especialesunclassified
“…Se recomienda iniciar la NP aportando 60 kcal/kg/día, con incrementos hasta 90-100 kcal/kg/día en la primera semana y hasta 120 a la tercera semana (21,22) (Tabla II). Sin embargo esta pauta aún es escasamente implementada en las unidades neonatales (19).…”
Section: Circunstancias Especialesunclassified
“…In another study, 44% of premature infants accumulated a deficit of more than 1 SD in weight during their stay in the NICU, and the percentage of children with cumulative weight deficits of more than two SDs increased from 14% at birth to 55% at discharge; at least 50% of this variability was attributed to nutrition (8). In addition, recommended nutrition goals are frequently not achieved, especially in the first weeks of life, and therefore considerable nutrient deficits can be expected in a high percentage of VLBW infants (9).…”
Section: Introductionmentioning
confidence: 99%